Macroeconomic Determinants of Banks’ Credit Risk: The Case of Bahrain - Madbouly, Araby (Journal of Asian Business Strategy, 2020)
The aim of this research is to point out the macroeconomic variables which significantly effect (determine) the banks’ credit risk (CR) in Bahrain. To acquire this aim, exploratory analysis design has been deployed. The sample of this study includes the seven listed banks in Bahraini bourse. Quarterly data collected about the research variables over the period 2009-Q1-2019-Q3. The banks’ CR in this research is measured by non-performing loans ratio. Regression model was implemented to test the impact of three selected macroeconomic variables on Bahraini banks’ credit risk. The analyses found that inflation significantly effect the banks CR and this relationship is positive while the Real Gross Domestic Product growth and oil returns significantly and positively effect it. The implication of this research highlights the credit policy makers in Bahraini banks the macroeconomic variables which could be taken into consideration to sidestep any drop in the loans repayment, this will avoid falling into banking crisis. The main limitation faced the researcher in this study is the test impact of the three macroeconomic variables only on the banks CR. although that it’s justifiable, it is suggested to include more macroeconomic factors such as international reserves and unemployment rate or related to the banks such as loan growth rate; capital adequacy; loan to deposit ratio and income diversification.